Preliminary Contamination Risk Assessment of Mining Waste Using Spatial Analysis and Geochemical Characterization of Rock Formations. Case Study in Hungary - Abdelaal, Ahmed (Journal of Environmental Geography, 2014)
The Mine Waste Directive (2006/21/EC) requires the risk-based inventory of all mine waste sites in Europe. The geochemical documentation concerning inert classification and ranking of the mine wastes requires specific field study and laboratory testing and analyses of waste material to assess the Acid Mine Drainage potential and toxic element mobility. The procedure applied in this study used a multi-level decision support scheme for the inert classification of waste rock material including: 1) expert judgment, 2) data review, 3) representative field sampling and laboratory analysis and testing of rock formations listed in the National Inert Mining Waste List, and 4) requesting available laboratory analysis data from selected operating mines. Based on a preliminary expert judgment, the listed formations were classified into three categories. A: inert B: probably inert, but has to be checked, C: probably not inert, has to be examined. This paper discusses the heavy metal contamination risk assessment (RA) in the Hungarian quarrymine waste sites. In total 30 waste sites (including both abandoned mines and active quarries) were selected for scientific testing using the EU Pre-selection Protocol. Altogether 93 field samples were collected from the waste sites including andesite, rhyolite, coal (lignite and black coals), peat, alginite, bauxite, clay and limestone. Laboratory analyses of the total toxic element content (aqua regia extraction), the mobile toxic element content (deionized water leaching) carried out according to the Hungarian GKM Decree No. 14/2008. (IV.3) concerning mining waste management. A detailed geochemical study together with spatial analysis and GIS were performed to derive a geochemically sound contamination RA of the mine waste sites. Key parameters such as heavy metals, in addition to the landscape metric parameter such as the distance to the nearest surface and ground water bodies, or to sensitive receptors such as settlements and protected areas calculated and statistically evaluated in order to calibrate the RA methods. Results show that some of the waste rock materials, assumed to be inert, were found non-inert. Thus, regional RA needs more spatial and petrological examination with special care to rock and mineral deposit genetics.